A Cross-Level Traceable Modeling for Hybrid Quantum–Classical Software - Sepúlveda, Samuel; Navarro, Claudio; Cravero, Ania; Moguel, Enrique (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Hybrid quantum–classical software requires engineering approaches that connect stakeholder goals, variability decisions, and architecture under NISQ constraints. We present Quantum Variability Management (QVM), a lightweight, requirements-driven modeling approach that integrates iStar, UVL, and Quantum-UML, through explicit cross-level traceability. QVM defines five rules that relate goals to features, constraints, component stereotypes, and configuration properties such as the provider and qubits. QVM focuses on the requirement-to-variability-to-architecture chain and on the auditable propagation of design changes. We assess the proposal through a scenario-based walkthrough in a logistics case, showing how changes in strategic intent, backend selection, and hardware quality assumptions can be propagated consistently across the three levels. The proposal provides a foundation for controlled reconfiguration in HQC systems, while broader user studies, multi-domain replications, and full tool integration remain future work.